2009
DOI: 10.1017/s0022112008005168
|View full text |Cite
|
Sign up to set email alerts
|

A generalized vortex ring model

Abstract: A conventional laminar vortex ring model is generalized by assuming that the time dependence of the vortex ring thickness is given by the relation = a t b , where a is a positive number and 1/4 6 b 6 1/2. In the case in which a = √ 2ν, where ν is the laminar kinematic viscosity, and b = 1/2, the predictions of the generalized model are identical with the predictions of the conventional laminar model. In the case of b = 1/4 some of its predictions are similar to the turbulent vortex ring models, assuming that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…For example, variations in energy over time were accurately captured, while circulation decay and the evolution of the translational velocity were predicted fairly well, which enables us to recommend the model for practical engineering applications. The fit with DNS data could be further improved if a power different to 1/2 was considered in expression (4.2) was considered; it was earlier shown that the Kaplanski-Rudi model for viscous vortex ring could be generalised for power-laws with exponents between 0.25 and 0.5 (see Kaplanski et al (2009)). The main aim of this paper, however, is not to find the best fit with DNS data but to assess the general capabilities of the model to reproduce realistic confined vortex rings.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, variations in energy over time were accurately captured, while circulation decay and the evolution of the translational velocity were predicted fairly well, which enables us to recommend the model for practical engineering applications. The fit with DNS data could be further improved if a power different to 1/2 was considered in expression (4.2) was considered; it was earlier shown that the Kaplanski-Rudi model for viscous vortex ring could be generalised for power-laws with exponents between 0.25 and 0.5 (see Kaplanski et al (2009)). The main aim of this paper, however, is not to find the best fit with DNS data but to assess the general capabilities of the model to reproduce realistic confined vortex rings.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The generalisation of Eq (2.7) for turbulent vortex rings was discussed by Kaplanski et al (2009). The Reynolds number of the flow is introduced as Re = Γ 0 /ν and the parameter ε = R 0 /R w < 1 quantifies the confinement of the vortex ring.…”
Section: Introductionmentioning
confidence: 99%
“…12 In the case b = 1/4 some of the predictions of Eqs. (1)-(6) are similar to the turbulent vortex ring models, assuming that the time-dependent effective viscosity ν * (introduced instead of ν) is equal to L L .…”
Section: Introductionmentioning
confidence: 99%